SOCIAL NETWORK ANALYSIS OF MANGOSTEEN TECHNOLOGY DEVELOPMENT CLUSTER IN INDONESIA BASED ON PATENT DOCUMENT APPLICATION - Yaman, Aris; Aris Kartika, Yulia; Tsurayya, Silmi; Ankafia, Adi; P. Manik, Lindung; Akbar, Zaenal; Indrawati, Ariani (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2022)
Functional food consumption is on the rise and has a significant market value. Indonesia is one of the largest mangosteens (a functional food source commodity) exporting countries globally. Unfortunately, the mangosteen export is still in fresh fruit condition, not in other forms that have a higher value. Policymakers need to identify critical technologies in the development of mangosteen commodities. This study uses a patent-based technology document analysis method to map the potential of technology. The data used is patent data that has been registered with the Indonesian Patent Office and the WIPO Patentscope database. The analysis was carried out using computational methods, namely a Social Network Analysis with the Girvan-Newman algorithm. According to the study's findings based on global patent data, there are three major technology clusters used in mangosteen patents: 1) 24 percent for technology related to developing preparations for medical, dental, or toilet purposes (A61K). 2) 20% for food and food ingredient technology or non-alcoholic beverages (A23L). The remaining 43 percent is spread across many other IPC technology codes, including technology related to drug preparations (A61P). It is in line with the results of patent data analysis in Indonesia, which also shows that there are three dominant technology groups applied to mangosteen in Indonesia, namely 1) Technology related to the development of medical, dental, and toilet technology (A61K) of 47 percent; 2) Technology related to food and food ingredients or non-alcoholic drinks (A23L) by 18 percent, and 3) Technology related to drug preparations (A61P) by 13 percent and the remaining 22 percent spread over several other IPC technology codes. According to Social Network Analysis, the world's dominant technology cluster for mangosteen is technology related to the development of food and food ingredients or non-alcoholic beverages (A23L). The technology associated with medical, dental, and toilet technology is the most important mangosteen technology cluster in Indonesia (A61K).